Aqueous electrolyte and aqueous battery
Patent Information
- Application Number
- CN202611331958.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-09
AI Technical Summary
对于水系磷酸铁锂/锌杂化电池而言,若仍采用“锌负极添加剂+普通成膜添加剂”的常规思路,难以同时解决磷酸铁锂类正极Fe溶出与锌负极沉积/剥离失稳等问题
本申请提供了一种低盐的水系电解液,不依赖于高浓度盐包水体系或高含量易燃有机电解液,其包含的跨电极选择性界面稳态添加剂组合物通过在水系环境中分别响应正极与负极的界面,使两者界面同步达到稳定状态,具体体现为:一方面,在锌负极一侧通过吸附、配位、络合或界面成膜作用调节Zn2+的沉积与剥离行为,均化界面离子通量,并诱导形成含Zn、O、P或C元素的复合界面层;另一方面,在磷酸铁锂正极一侧通过抑制Fe2+/Fe3+的溶出并促进形成含磷或含氟磷组分的界面钝化层,同时利用第一添加剂来降低自由水的活性和局部pH的波动,从而实现磷酸铁锂正极Fe溶出抑制、锌负极沉积导向及类SEI膜构筑和水结构稳态调控的技术效果。
Smart Images

Figure CN122889859A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of electrolyte technology, specifically relating to an aqueous electrolyte and an aqueous battery. Background Technology
[0002] Aqueous batteries use water as the main solvent and offer advantages such as high safety, high ionic conductivity, low cost, and environmental friendliness. Among these, zinc metal anodes are widely used in aqueous zinc-ion battery systems due to their high theoretical capacity, abundant resources, low price, and good compatibility with aqueous systems. However, traditional aqueous zinc-ion batteries have long been plagued by problems such as hydrogen evolution, corrosion, dendrite growth, and accumulation of alkaline byproducts at the zinc anode. To address these issues, existing technologies have proposed numerous electrolyte additive schemes, primarily aiming to mitigate these problems by controlling the zinc anode interface and adjusting the water molecule structure.
[0003] However, the structure of aqueous lithium iron phosphate / zinc hybrid batteries differs significantly from that of conventional aqueous zinc-ion batteries. In this hybrid battery system, Li... + The reversible insertion and extraction mainly occur in lithium iron phosphate cathodes, while Zn... 2+ The deposition and stripping mainly occur on the zinc anode. It is this "dual-carrier operation" mechanism that determines that the electrolyte design cannot only focus on the zinc anode side, but must simultaneously consider the interface stability requirements of both the lithium iron phosphate cathode and the zinc anode.
[0004] In practical applications, lithium iron phosphate cathodes in aqueous environments may be affected by factors such as free water, acidic species, local pH fluctuations, or interfacial side reactions, leading to surface structure damage and Fe... 2+ / Fe 3+ Leaching. On the one hand, Fe leaching not only causes the loss of positive electrode active material, but may also migrate to the negative electrode side and interfere with the zinc ion deposition / stripping process. On the other hand, Zn still exists in the aqueous electrolyte at the zinc negative electrode. 2+ Problems include uneven flux, dendrite growth, hydrogen evolution, corrosion, and the formation of dead zinc.
[0005] Currently, most electrolyte additives for aqueous zinc-ion batteries are geared towards addressing the single zinc anode problem, or they combine known substances such as conventional metal ion complexing agents or film-forming agents. For aqueous lithium iron phosphate / zinc hybrid batteries, if the conventional approach of "zinc anode additive + ordinary film-forming additive" is still adopted, it is difficult to simultaneously solve the problems of Fe dissolution in lithium iron phosphate cathodes and instability in zinc anode deposition / stripping.
[0006] Therefore, there is an urgent need to develop an electrolyte solution specifically designed for aqueous lithium iron phosphate / zinc hybrid batteries, based on the requirement for stable cross-electrode interfaces between the positive and negative electrodes, in order to solve the above problems. Summary of the Invention
[0007] To address the shortcomings of existing technologies, the purpose of this application is to provide an aqueous electrolyte that can comprehensively improve the positive electrode structural stability, zinc negative electrode reversibility, and cycle stability of aqueous lithium iron phosphate / zinc hybrid batteries without relying on high-concentration salt-encapsulated water systems and high-content flammable organic electrolytes.
[0008] To achieve this objective, the present application adopts the following technical solution: In a first aspect, this application provides an aqueous electrolyte comprising zinc salt, lithium salt, an additive composition, and water, wherein the additive composition comprises a first additive, a second additive, and a third additive. The first additive includes an amphoteric compound; The structure of the second additive includes at least one of phosphonic acid group, phosphate group, carboxyl group or hydroxyl group; The third additive includes at least one of phosphate, fluorophosphate, pyrophosphate, metaphosphate, or phosphite.
[0009] Unlike conventional additives that only address a single problem in the zinc anode (hydrogen evolution or dendrite formation), the cross-electrode selective interface stabilization additive composition provided in this application achieves a stable state simultaneously at the interfaces of the positive and negative electrodes in an aqueous environment by responding separately to these interfaces. Specifically, on the one hand, it regulates the Zn content on the zinc anode side through adsorption, coordination, complexation, or interfacial film formation. 2+ The deposition and stripping behavior of the lithium iron phosphate cathode is improved, the interfacial ion flux is homogenized, and the formation of a composite interfacial layer containing Zn, O, P, or C elements is induced. On the other hand, the Fe content is suppressed on the lithium iron phosphate cathode side. 2+ / Fe 3+ The dissolution of phosphorus and the formation of an interface passivation layer containing phosphorus or fluorine-containing phosphorus components are promoted. At the same time, the first additive is used to reduce the activity of free water and the fluctuation of local pH, thereby achieving the technical effects of inhibiting the dissolution of Fe in lithium iron phosphate cathode, guiding the deposition of zinc anode, constructing SEI-like membranes, and regulating the steady state of water structure.
[0010] The “cross-electrode selective interface steady state” described in this application specifically refers to the multi-level synergistic effect of the functional additives in the electrolyte not only playing a role on one side of a certain electrode, but forming a bulk water structure steady state, zinc negative electrode side deposition guidance and SEI-like film construction, lithium iron phosphate positive electrode side Fe dissolution inhibition and interface passivation in the same zinc salt / lithium salt water electrolyte.
[0011] In some embodiments, the first additive is selected from at least one of betaine, sulfobetaine, carboxybetaine, glycine betaine, proline, glycine or taurine, preferably betaine.
[0012] In some embodiments, the molar concentration of the first additive in the aqueous electrolyte is 20 mmol / L to 200 mmol / L, for example, it can be 20 mmol / L, 50 mmol / L, 80 mmol / L, 100 mmol / L, 120 mmol / L, 150 mmol / L, 180 mmol / L or 200 mmol / L, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0013] In some preferred embodiments, the molar concentration of the first additive in the aqueous electrolyte is 50 mmol / L to 150 mmol / L, for example, it can be 50 mmol / L, 60 mmol / L, 80 mmol / L, 100 mmol / L, 110 mmol / L, 120 mmol / L, 140 mmol / L or 150 mmol / L, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0014] In this application, by adjusting the type and molar concentration of the first additive to a suitable range, the aforementioned zwitterionic or amino acid compounds can further regulate the hydrogen bond network of water molecules through hydrogen bonding or ion-dipole interactions, reducing free water activity and mitigating local pH fluctuations, thus providing a bulk aqueous environment basis for the stability of the positive and negative electrode interfaces. Using a higher molar concentration of the first additive can easily lead to increased electrolyte viscosity, increased interfacial impedance, or decreased ion transport.
[0015] In some embodiments, the second additive is selected from at least one of hydroxyethylidene diphosphonate, aminotrimethylidene phosphonate, ethylenediaminetetramethylidene phosphonate, diethylenetriaminepentamethylidene phosphonate, phytate, citrate, or tartrate.
[0016] In some preferred embodiments, the second additive is selected from at least one of tetrasodium hydroxyethylidene diphosphonate, disodium hydroxyethylidene diphosphonate, potassium hydroxyethylidene diphosphonate, lithium hydroxyethylidene diphosphonate, sodium aminotrimethylidene phosphonate, lithium aminotrimethylidene phosphonate, or sodium phytate.
[0017] In some embodiments, the molar concentration of the second additive in the aqueous electrolyte is 0.05 mmol / L to 10 mmol / L, for example, it can be 0.05 mmol / L, 0.1 mmol / L, 0.5 mmol / L, 1 mmol / L, 2 mmol / L, 5 mmol / L, 8 mmol / L or 10 mmol / L, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0018] In some preferred embodiments, the molar concentration of the second additive in the aqueous electrolyte is 0.1 mmol / L to 5 mmol / L, for example, it can be 0.1 mmol / L, 0.2 mmol / L, 0.5 mmol / L, 0.8 mmol / L, 1 mmol / L, 1.5 mmol / L, 2 mmol / L, 2.5 mmol / L, 3 mmol / L, 3.5 mmol / L, 4 mmol / L, 4.5 mmol / L or 5 mmol / L, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0019] In this application, by adjusting the type and molar concentration of the second additive to a suitable range, the structure of the second additive includes phosphonic acid groups, phosphate groups, carboxylic acid groups, or polyhydroxy coordination structures, thereby enabling it to react with Zn. 2+ Alternatively, coordination, adsorption, or complexation may occur on the zinc anode surface, thereby homogenizing Zn. 2+ Interfacial flux is increased, reducing the concentration of local electric fields and promoting the formation of a phosphorus-containing organic-inorganic composite interfacial layer during cycling. However, using a second additive with a high molar concentration can easily lead to increased electrolyte viscosity, increased interfacial impedance, or decreased ion transport.
[0020] In some embodiments, the third additive is selected from at least one of monofluorophosphate, dihydrogen phosphate, hydrogen phosphate, glycerol phosphate, pyrophosphate, metaphosphate, or phosphite.
[0021] In some preferred embodiments, the third additive is selected from at least one of sodium monofluorophosphate, lithium monofluorophosphate, potassium monofluorophosphate, lithium dihydrogen phosphate, sodium dihydrogen phosphate, lithium hydrogen phosphate, disodium hydrogen phosphate, or sodium glycerophosphate.
[0022] In some embodiments, the molar concentration of the third additive in the aqueous electrolyte is 1 mmol / L to 50 mmol / L, for example, it can be 1 mmol / L, 5 mmol / L, 10 mmol / L, 20 mmol / L, 30 mmol / L, 40 mmol / L or 50 mmol / L, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0023] In some preferred embodiments, the molar concentration of the third additive in the aqueous electrolyte is 5 mmol / L to 30 mmol / L, for example, it can be 5 mmol / L, 8 mmol / L, 10 mmol / L, 15 mmol / L, 20 mmol / L, 25 mmol / L or 30 mmol / L, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0024] In this application, by adjusting the type and molar concentration of the third additive to a suitable range, the third additive can provide phosphate, fluorophosphate, or related phosphorus-containing microenvironments at the lithium iron phosphate cathode / aqueous electrolyte interface, reducing the erosion of the cathode surface by free water or acidic species, and promoting the formation of a passivation interface containing phosphorus or fluorophosphate components, thereby inhibiting Fe 2+ / Fe 3+ Dissolution. If a third additive with a higher molar concentration is used, it can easily lead to increased electrolyte viscosity, increased interfacial impedance, or decreased ion transport.
[0025] In some embodiments, the molar concentration of zinc salt in the aqueous electrolyte is 0.2 mol / L to 1.5 mol / L, for example, it can be 0.2 mol / L, 0.5 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L or 1.5 mol / L, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0026] In some preferred embodiments, the molar concentration of zinc salt in the aqueous electrolyte is 0.3 mol / L to 1.0 mol / L, for example, it can be 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.8 mol / L or 1.0 mol / L, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0027] In some embodiments, the zinc salt is selected from at least one of zinc sulfate, zinc trifluoromethanesulfonate, zinc acetate, zinc methanesulfonate, or zinc nitrate, preferably zinc sulfate, thereby providing the Zn required for zinc anode deposition and stripping. 2+ .
[0028] In some embodiments, the molar concentration of lithium salt in the aqueous electrolyte is 0.5 mol / L to 3.0 mol / L, for example, it can be 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L or 3.0 mol / L, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0029] In some preferred embodiments, the molar concentration of lithium salt in the aqueous electrolyte is 1.0 mol / L to 2.5 mol / L, for example, it can be 1.0 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2.0 mol / L or 2.5 mol / L, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0030] In some embodiments, the lithium salt is selected from at least one of lithium sulfate, lithium trifluoromethanesulfonate, lithium acetate, lithium methanesulfonate, lithium nitrate, lithium dihydrogen phosphate, or lithium hydrogen phosphate, preferably lithium sulfate, thereby providing the Li required for the insertion and extraction of lithium iron phosphate cathodes. + .
[0031] In this application, by introducing the above-mentioned additive composition into a low-concentration zinc and lithium salt dual-salt electrolyte, the bulk water structure, the lithium iron phosphate cathode interface, and the zinc anode interface are simultaneously regulated.
[0032] Preferably, the additive composition comprises 50 mmol / L to 150 mmol / L of betaine, 0.05 mmol / L to 1 mmol / L of tetrasodium hydroxyethylidene bisphosphonate, and 3 mmol / L to 20 mmol / L of sodium monofluorophosphate; more preferably, it comprises 100 mmol / L of betaine, 0.1 mmol / L of tetrasodium hydroxyethylidene bisphosphonate, and 5 mmol / L of sodium monofluorophosphate. The additive composition within the above specific concentration range can participate in the transelectrode interface steady-state regulation process through hydrogen bonding, metal ion coordination, or the action of a phosphorus-containing interface passivation layer.
[0033] In some embodiments, the aqueous electrolyte further includes an organic solvent.
[0034] As an example, the organic solvent includes any one or a combination of at least two of propylene glycol, butanediol, ethylene glycol, or pentanediol.
[0035] In some embodiments, with the total volume of the aqueous electrolyte being 100%, the volume percentage of the organic solvent is less than 10%, for example, it can be 2%, 4%, 6%, 8% or 9%, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0036] Secondly, this application provides a method for preparing an aqueous electrolyte as described in the first aspect, the method comprising the following steps: At room temperature (25°C), a mixture of zinc salt, lithium salt, additives, and water is stirred to obtain the aqueous electrolyte. The additive composition includes a first additive, a second additive, and a third additive; The first additive includes an amphoteric compound; The structure of the second additive includes at least one of phosphonic acid group, phosphate group, carboxyl group or hydroxyl group; The third additive includes at least one of phosphate, fluorophosphate, pyrophosphate, metaphosphate, or phosphite.
[0037] In some embodiments, the stirring time is 10 min to 120 min, for example, it can be 10 min, 20 min, 50 min, 80 min, 100 min or 120 min, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0038] In some preferred embodiments, the stirring time is 30 min to 60 min, for example, 30 min, 40 min, 50 min, or 60 min, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0039] Thirdly, this application provides an aqueous battery, which includes a positive electrode, a negative electrode, an electrolyte, and a separator. The electrolyte includes the aqueous electrolyte according to the first aspect. The positive electrode active material includes at least one of carbon-coated lithium iron phosphate, lithium iron phosphate, lithium manganese iron phosphate, or doped lithium iron phosphate. The negative electrode active material includes at least one of zinc foil, zinc sheet, zinc powder composite electrode, porous zinc electrode, zinc alloy electrode, or zinc-based material loaded on a conductive substrate.
[0040] In some embodiments, the positive electrode further includes a positive electrode current collector, which is selected from at least one of titanium foil, stainless steel foil, carbon paper, carbon cloth, graphite film, carbon-coated aluminum foil, or carbon-coated titanium foil.
[0041] In some embodiments, the diaphragm is selected from at least one of glass fiber diaphragm, cellulose diaphragm, hydrophilic polyolefin diaphragm, hydrophilic PP membrane or composite nonwoven diaphragm.
[0042] The numerical range described in this application includes not only the point values listed above, but also any point values within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific point values included in the range.
[0043] Compared with the prior art, this application has the following advantages: This application provides a low-salt aqueous electrolyte that does not rely on high-concentration brine systems or high-content flammable organic electrolytes. The electrolyte contains a transelectrode selective interfacial stabilizing additive composition that, in an aqueous environment, responds separately to the interfaces of the positive and negative electrodes, enabling both interfaces to reach a stable state synchronously. Specifically, on the zinc negative electrode side, Zn is regulated through adsorption, coordination, complexation, or interfacial film formation. 2+ The deposition and stripping behavior of the lithium iron phosphate cathode is improved, the interfacial ion flux is homogenized, and the formation of a composite interfacial layer containing Zn, O, P, or C elements is induced. On the other hand, the Fe content is suppressed on the lithium iron phosphate cathode side. 2+ / Fe 3+The dissolution of phosphorus and the formation of an interface passivation layer containing phosphorus or fluorine-containing phosphorus components are promoted. At the same time, the first additive is used to reduce the activity of free water and the fluctuation of local pH, thereby achieving the technical effects of inhibiting the dissolution of Fe in lithium iron phosphate cathode, guiding the deposition of zinc anode, constructing SEI-like membranes, and regulating the steady state of water structure.
[0044] In addition, the aqueous electrolyte provided in this application is readily available and easy to prepare, and has good industrial applicability. Attached Figure Description
[0045] Figure 1 This is a schematic diagram illustrating the mechanism of action of the aqueous electrolyte in an aqueous lithium iron phosphate / zinc hybrid battery provided in this application.
[0046] Figure 2 The bar chart shows the Fe dissolution test results of the carbon-coated lithium iron phosphate cathode sheets provided in Example 1 and Comparative Examples 1-5.
[0047] Figure 3 Cyclic performance diagrams of Zn||Zn symmetric button cells provided in Example 1 and Comparative Examples 1-5.
[0048] Figure 4 The graph shows the cycle performance of the aqueous lithium iron phosphate / zinc button batteries assembled in Example 1 and Comparative Examples 1-5.
[0049] Figure 5 In the Zn||Cu button cells assembled in Example 1 and Comparative Example 1, the copper foil was subjected to static wetting and then subjected to a 1 mA / cm 2 1mAh / cm 2 SEM image of the surface morphology after 100 cycles under the given conditions, with a scale bar of 10 μm. Detailed Implementation
[0050] The technical solution of this application will be further described below with reference to specific embodiments and accompanying drawings. Those skilled in the art should understand that the embodiments described are merely illustrative of this application and should not be construed as specific limitations thereof.
[0051] Unless otherwise stated, the zinc sulfate (ZnSO4), lithium sulfate (Li2SO4), additives, lithium iron phosphate, conductive agents, binders, separators, zinc foil, and current collectors used in the following examples and comparative examples are all commercially available. The water used is ultrapure water with a resistivity of not less than 18 MΩ·cm. All aqueous electrolytes can be prepared by stirring at room temperature without the need for an inert atmosphere, high temperature and pressure, or complex post-treatment steps.
[0052] As described in the background section, current aqueous zinc-ion battery electrolyte additives are mostly geared towards addressing the single zinc anode problem, or they combine known substances such as conventional metal ion complexing agents or film-forming agents. For aqueous lithium iron phosphate / zinc hybrid batteries, if the conventional approach of "zinc anode additive + ordinary film-forming additive" is still adopted, it is difficult to simultaneously solve the problems of Fe dissolution in lithium iron phosphate cathodes and zinc anode deposition / stripping instability. Therefore, if... Figure 1 As shown, this application introduces an additive composition into a low-concentration ZnSO4 / Li2SO4 dual-salt electrolyte to simultaneously and stably regulate the bulk water structure, the lithium iron phosphate cathode interface, and the zinc anode interface.
[0053] The technical solution of this application will be further illustrated below through specific embodiments.
[0054] Example 1 This embodiment provides an aqueous electrolyte comprising zinc sulfate, lithium sulfate, an additive composition, and water. The additive composition comprises a first additive, a second additive, and a third additive.
[0055] The first additive is betaine; the second additive is tetrasodium hydroxyethylidene diphosphonate; and the third additive is sodium monofluorophosphate.
[0056] In the aqueous electrolyte, the molar concentration of the first additive is 100 mmol / L, the molar concentration of the second additive is 0.1 mmol / L, and the molar concentration of the third additive is 5 mmol / L. The molar concentration of zinc sulfate is 0.5 mol / L, and the molar concentration of lithium sulfate is 2.0 mol / L.
[0057] This embodiment also provides a method for preparing the above-mentioned aqueous electrolyte, which includes the following steps: At 25°C, zinc sulfate and lithium sulfate were weighed and dissolved in deionized water to prepare a basic electrolyte, wherein the molar concentration of zinc sulfate was 0.5 mol / L and the molar concentration of lithium sulfate was 2.0 mol / L.
[0058] Betaine was added to the above-mentioned basic electrolyte to bring its final molar concentration to 100 mmol / L, followed by tetrasodium hydroxyethylidene diphosphonate to bring its final molar concentration to 0.1 mmol / L; then sodium monofluorophosphate was added to bring its final molar concentration to 5 mmol / L. The mixture was stirred for 45 min until all components were completely dissolved to obtain the aqueous electrolyte.
[0059] Example 2 This embodiment provides an aqueous electrolyte comprising zinc sulfate, lithium sulfate, an additive composition, and water. The additive composition comprises a first additive, a second additive, and a third additive.
[0060] The first additive is betaine; the second additive is tetrasodium hydroxyethylidene diphosphonate; and the third additive is sodium monofluorophosphate.
[0061] In the aqueous electrolyte, the molar concentration of the first additive is 20 mmol / L, the molar concentration of the second additive is 10 mmol / L, and the molar concentration of the third additive is 50 mmol / L. The molar concentration of zinc sulfate is 0.2 mol / L, and the molar concentration of lithium sulfate is 3.0 mol / L.
[0062] This embodiment also provides a method for preparing the above-mentioned aqueous electrolyte, which includes the following steps: At 25°C, zinc sulfate and lithium sulfate were weighed and dissolved in deionized water to prepare a basic electrolyte, wherein the molar concentration of zinc sulfate was 0.2 mol / L and the molar concentration of lithium sulfate was 3.0 mol / L.
[0063] Betaine was added to the above-mentioned basic electrolyte to bring its final molar concentration to 20 mmol / L, followed by tetrasodium hydroxyethylidene diphosphonate to bring its final molar concentration to 10 mmol / L; then sodium monofluorophosphate was added to bring its final molar concentration to 50 mmol / L. The mixture was stirred for 30 min until all components were completely dissolved to obtain the aqueous electrolyte.
[0064] Example 3 This embodiment provides an aqueous electrolyte comprising zinc sulfate, lithium sulfate, an additive composition, and water. The additive composition comprises a first additive, a second additive, and a third additive.
[0065] The first additive is betaine; the second additive is tetrasodium hydroxyethylidene diphosphonate; and the third additive is sodium monofluorophosphate.
[0066] In the aqueous electrolyte, the molar concentration of the first additive is 200 mmol / L, the molar concentration of the second additive is 0.05 mmol / L, and the molar concentration of the third additive is 1 mmol / L. The molar concentration of zinc sulfate is 1.5 mol / L, and the molar concentration of lithium sulfate is 0.5 mol / L.
[0067] This embodiment also provides a method for preparing the above-mentioned aqueous electrolyte, which includes the following steps: At 25°C, zinc sulfate and lithium sulfate were weighed and dissolved in deionized water to prepare a basic electrolyte, wherein the molar concentration of zinc sulfate was 1.5 mol / L and the molar concentration of lithium sulfate was 0.5 mol / L.
[0068] Betaine was added to the above-mentioned basic electrolyte to bring its final molar concentration to 200 mmol / L, followed by tetrasodium hydroxyethylidene diphosphonate to bring its final molar concentration to 0.05 mmol / L; then sodium monofluorophosphate was added to bring its final molar concentration to 1 mmol / L. The mixture was stirred for 60 min until all components were completely dissolved to obtain the aqueous electrolyte.
[0069] Example 4 The difference between this embodiment and Embodiment 1 is that the molar concentration of the first additive in the aqueous electrolyte is 400 mmol / L, and the total mass of all components in the electrolyte is increased to 100% by adjusting the water content. Everything else is the same as in Embodiment 1.
[0070] Example 5 The difference between this embodiment and Example 1 is that the tetrasodium hydroxyethylidene diphosphonate in the second additive is replaced with sodium citrate of equal molar concentration; otherwise, they are the same as in Example 1.
[0071] Example 6 The difference between this embodiment and Embodiment 1 is that, except for adjusting the molar concentration of the second additive in the electrolyte additive to 0.01 mmol / L and increasing the content of the first and third additives by an equal molar ratio, everything else is the same as in Embodiment 1.
[0072] Example 7 The difference between this embodiment and Example 1 is that, except for adjusting the molar concentration of the second additive in the additive composition to 20 mmol / L and reducing the content of the first and third additives by the same mass ratio, everything else is the same as in Example 1.
[0073] Example 8 The difference between this embodiment and Example 1 is that, except for adjusting the molar concentration of the third additive in the additive composition to 0.5 mmol / L and increasing the content of the first and second additives by an equal molar ratio, everything else is the same as in Example 1.
[0074] Example 9 The difference between this embodiment and Embodiment 1 is that, except for adjusting the molar concentration of the third additive in the electrolyte additive to 60 mmol / L and reducing the content of the first and second additives by an equal molar ratio, everything else is the same as in Embodiment 1.
[0075] Comparative Example 1 The difference between this comparative example and Example 1 is that, except that the electrolyte additives are not contained in the first additive, the second additive and the third additive are replaced with water in equal molar amounts, they are the same as in Example 1.
[0076] Comparative Example 2 The difference between this comparative example and Example 1 is that, except for adjusting the electrolyte additive to contain only the first additive and replacing the second and third additives with water in equal molar amounts, everything else is the same as Example 1.
[0077] Comparative Example 3 The difference between this comparative example and Example 1 is that, except for adjusting the electrolyte additive to contain only the second additive and replacing the first and third additives with water in equal molar amounts, everything else is the same as Example 1.
[0078] Comparative Example 4 The difference between this comparative example and Example 1 is that, except for adjusting the electrolyte additive to contain only the third additive and replacing the first and second additives with water in equal molar amounts, everything else is the same as Example 1.
[0079] Comparative Example 5 The difference between this comparative example and Example 1 is that, except for adjusting the electrolyte additive to contain only the second and third additives and replacing the first additive with water in equal molar amounts, everything else is the same as in Example 1.
[0080] Application Examples 1-9 and Comparative Application Examples 1-5 The aqueous electrolytes provided in Examples 1-9 and Comparative Examples 1-5 were used to assemble aqueous lithium iron phosphate / zinc button batteries and aqueous lithium iron phosphate / zinc hybrid pouch batteries, respectively. The specific preparation methods are as follows: (1) Assembly of aqueous lithium iron phosphate / zinc button batteries Carbon-coated lithium iron phosphate, Super P conductive agent and polyvinylidene fluoride binder are mixed in a mass ratio of 80:10:10, and an appropriate amount of N-pyrrolidone is added and stirred to form a uniform positive electrode slurry.
[0081] The obtained positive electrode slurry was coated onto the surface of carbon-coated aluminum foil fluid and dried at 80°C for 9 hours. It was then rolled and punched into positive electrode sheets with a diameter of 14 mm. The loading of the positive electrode active material was 6 mg / cm³. 2 .
[0082] Zinc foil with a diameter of 14 mm was used as the negative electrode, and it was washed with deionized water and ethanol in sequence and then dried for later use.
[0083] The diaphragm is made of glass fiber.
[0084] Assemble the button cell in the following order: negative electrode shell, spring contact, gasket, zinc negative electrode, separator, lithium iron phosphate positive electrode sheet, and positive electrode shell. Add 120 μL of the above-mentioned aqueous electrolyte to each button cell to ensure that the separator and electrodes are fully wetted. After assembly, let it stand for 10 hours to allow the electrolyte to fully wet the electrodes and separator, thus obtaining an aqueous lithium iron phosphate / zinc button cell.
[0085] (2) Assembly of aqueous lithium iron phosphate / zinc hybrid pouch cells The carbon-coated lithium iron phosphate cathode slurry formulation, coating, and drying process are the same as those for the aforementioned button battery. The cathode sheet is cut into double-sided coated sheets with an effective size of 30mm × 40mm, and the active material loading on one side of the cathode is 6mg / cm³. 2 A 50mAh battery cell was constructed using three double-sided coated positive electrode sheets and four zinc foil negative electrode sheets with an effective size of 32mm × 42mm, assembled in a Z-shaped stacking configuration with a glass fiber separator. 4.0mL of the aforementioned aqueous electrolyte was injected into the stacked cell, and after standing for 10 hours to ensure full wetting, it was vacuum-sealed using an aluminum-plastic film to obtain a 50mAh-class aqueous lithium iron phosphate / zinc hybrid soft-pack battery.
[0086] Test conditions The performance of the 50mAh-class aqueous lithium iron phosphate / zinc hybrid soft-pack battery, aqueous lithium iron phosphate / zinc button battery, Zn||Zn symmetric button battery, and Zn||Cu button battery prepared in the above embodiments and comparative examples were tested respectively, and the test methods are as follows: (1) Test of Fe dissolution in carbon-coated lithium iron phosphate cathode Fe dissolution tests were conducted using the aforementioned 50mAh-class aqueous lithium iron phosphate / zinc hybrid pouch cells. Two sets of pouch cells were assembled in parallel for each electrolyte: the first set was allowed to stand at room temperature for 14 days after electrolyte injection; the second set was first activated at 0.1 A / g for 3 cycles, then cyclicated at 0.5 A / g for 100 cycles. After the tests, the pouch cells were disassembled, the carbon-coated lithium iron phosphate cathode was removed, and the corresponding electrolyte was collected. The mass of the cathode active material and the amount of electrolyte injected were kept consistent across all pouch cell sets.
[0087] After soaking or circulating, the electrolyte was filtered and appropriately diluted. The Fe element content in the electrolyte was determined using ICP-OES. The Fe dissolution amount can be calculated using the following formula: Fe dissolution amount = Fe concentration in electrolyte × electrolyte volume / mass of positive electrode active material.
[0088] like Figure 2 As shown, by comparing the Fe concentration and normalized Fe dissolution amount in the aqueous electrolytes provided in the examples and comparative examples, the inhibitory effect of different additive combinations on Fe dissolution in carbon-coated lithium iron phosphate cathodes can be evaluated.
[0089] (2) Changes in pH and conductivity of the electrolyte The aforementioned 50mAh-class aqueous lithium iron phosphate / zinc hybrid pouch cell was used for testing. The pouch cell was first activated at 0.1 A / g for 3 cycles, and then cycled at 0.5 A / g for 100 cycles. After the cycling was completed, the cells were disassembled and the corresponding electrolyte was collected. The initial pH and initial conductivity were measured before the electrolyte was injected into the pouch cell.
[0090] The pH of the initial electrolyte and the recovered electrolyte in the pouch cell after 100 cycles were measured using a calibrated pH meter.
[0091] The conductivity of the initial electrolyte and the recovered electrolyte in the pouch cell after 100 cycles were measured using a conductivity meter.
[0092] By comparing the changes in pH and conductivity in the aqueous electrolytes provided in the examples and comparative examples, the effects of different additive combinations on the steady-state regulation of the water structure in the aqueous electrolytes can be evaluated.
[0093] (3) Testing of Zn||Zn symmetrical button cell and Zn||Cu button cell Zn||Zn symmetrical button cell: Two zinc foils with a diameter of 14 mm and the same thickness were used as symmetrical electrodes, and a glass fiber membrane was used as the separator. Aqueous electrolytes provided in the examples and comparative examples were added respectively to assemble CR2032 type Zn||Zn symmetrical button cells. The amount of electrolyte added to each cell was 140 μL.
[0094] Zn||Cu button cells: Using a 14mm diameter zinc foil as the counter electrode and a 14mm diameter copper foil as the working electrode, with a glass fiber membrane as the separator, CR2032 type Zn||Cu button cells were assembled by adding the aqueous electrolytes provided in the examples and comparative examples, respectively. The electrolyte addition amount in each cell was 140μL. Both types of button cells were subjected to constant current deposition / stripping tests after standing at room temperature for 8 hours, with the test conditions being 1mA / cm. 2 1mAh / cm 2 Record the polarization voltage and short-circuit time of the Zn||Zn button cell, and record the average coulombic efficiency and stable cycle number of the Zn||Cu button cell.
[0095] Figure 5 The morphology tests shown included two sets of Zn||Cu button cells: one set was left to stand and soak for only 8 hours, while the other set was cycled 100 times under the same conditions. After disassembly, the copper foil was removed, quickly rinsed with deionized water and ethanol, dried, and then the surface morphology of the copper foil was observed using SEM.
[0096] (4) Cyclic performance test Charge-discharge tests were conducted using the aqueous lithium iron phosphate / zinc button batteries provided in the above application examples and comparative application examples: the test voltage window was 0.8V~1.6V. During testing, three activation cycles were first performed at a rate of 0.1A / g, followed by a cycle test at a rate of 0.5A / g. Figure 4 As shown, the battery's discharge specific capacity and capacity retention rate are recorded.
[0097] By comparing the cycle stability of aqueous lithium iron phosphate / zinc hybrid batteries under different electrolytes, the impact of each solute combination on the overall performance of the battery can be evaluated.
[0098] The test results are shown in Tables 1-4.
[0099] Table 1 Based on Table 1 Figure 2 It can be seen that the Fe concentration and normalized Fe dissolution amount in Examples 1-3 are significantly lower than those in the comparative examples, with Example 1 showing the greatest reduction in Fe concentration. 2+ / Fe 3+ The dissolution effect is optimal; in Examples 4-9, the type or concentration of additives deviates from the preferred range, resulting in the inhibition of Fe 2+ / Fe 3+ The dissolution capacity was lower than in Example 1, indicating that the first, second, and third additives have a synergistic inhibitory effect on Fe within a suitable concentration range. 2+ / Fe 3+ The role of dissolution.
[0100] Table 2 As shown in Table 2, the pH and conductivity of the electrolyte in Examples 1-3 after 100 cycles of the aqueous lithium iron phosphate / zinc hybrid soft-pack battery showed relatively small changes, with Example 1 showing the smallest change. The stability of the electrolyte in Examples 4-9 was lower than that in Example 1. The pH and conductivity changes of the aqueous electrolyte in each comparative example were more significant overall, indicating that the preferred additive combination of the first, second, and third additives is beneficial to maintaining the stability of the electrolyte system.
[0101] Table 3 Based on Table 3 Figure 3 It can be seen that the short-circuit time of the Zn||Zn symmetric button cells in Examples 1-3 is longer, and the average coulombic efficiency and stable cycle number of the Zn||Cu button cells are higher. The relevant performance of Examples 4-9 is lower than that of Example 1, and the overall deposition / stripping performance of the cells corresponding to each comparative example is lower than that of Examples 1-3.
[0102] Table 4 As can be seen from Table 4, Examples 1-3 have higher discharge specific capacity and long-term cycle capacity retention capability; Examples 4-9 have lower overall cycle performance than Example 1 due to the type or concentration of additives deviating from the preferred range, and the overall capacity level and long-term cycle stability of each comparative example are lower than those of Examples 1-3.
[0103] The applicant declares that the above description is only a specific implementation of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application fall within the protection and disclosure scope of this application.
Claims
1. An aqueous electrolyte, characterized in that, The aqueous electrolyte comprises zinc salt, lithium salt, an additive composition, and water, wherein the additive composition comprises a first additive, a second additive, and a third additive. The first additive includes an amphoteric compound; The structure of the second additive includes at least one of phosphonic acid group, phosphate group, carboxyl group or hydroxyl group; The third additive includes at least one of phosphate, fluorophosphate, pyrophosphate, metaphosphate, or phosphite.
2. The aqueous electrolyte according to claim 1, characterized in that, The first additive is selected from at least one of betaine, sulfobetaine, carboxybetaine, glycine betaine, proline, glycine, or taurine; And / or, the molar concentration of the first additive in the aqueous electrolyte is 20 mmol / L to 200 mmol / L.
3. The aqueous electrolyte according to claim 1 or 2, characterized in that, The second additive is selected from at least one of hydroxyethylidene diphosphonate, aminotrimethylidene phosphonate, ethylenediaminetetramethylidene phosphonate, diethylenetriaminepentamethylidene phosphonate, phytate, citrate or tartrate; And / or, the molar concentration of the second additive in the aqueous electrolyte is 0.05 mmol / L to 10 mmol / L.
4. The aqueous electrolyte according to claim 3, characterized in that, The second additive is selected from at least one of tetrasodium hydroxyethylidene diphosphonate, disodium hydroxyethylidene diphosphonate, potassium salt of hydroxyethylidene diphosphonate, lithium salt of hydroxyethylidene diphosphonate, sodium salt of aminotrimethylidene phosphonate, lithium salt of aminotrimethylidene phosphonate, or sodium phytate. And / or, the molar concentration of the second additive in the aqueous electrolyte is 0.1 mmol / L to 5 mmol / L.
5. The aqueous electrolyte according to any one of claims 1 to 4, characterized in that, The third additive is selected from at least one of monofluorophosphate, dihydrogen phosphate, hydrogen phosphate, glycerol phosphate, pyrophosphate, metaphosphate, or phosphite. And / or, the molar concentration of the third additive in the aqueous electrolyte is 1 mmol / L to 50 mmol / L.
6. The aqueous electrolyte according to claim 5, characterized in that, The third additive is selected from at least one of sodium monofluorophosphate, lithium monofluorophosphate, potassium monofluorophosphate, lithium dihydrogen phosphate, sodium dihydrogen phosphate, lithium hydrogen phosphate, disodium hydrogen phosphate, or sodium glycerophosphate. And / or, the molar concentration of the third additive in the aqueous electrolyte is 5 mmol / L to 30 mmol / L.
7. The aqueous electrolyte according to any one of claims 1 to 6, characterized in that, The molar concentration of zinc salt in the aqueous electrolyte is 0.2 mol / L to 1.5 mol / L; And / or, the molar concentration of lithium salt in the aqueous electrolyte is 0.5 mol / L to 3.0 mol / L.
8. The aqueous electrolyte according to claim 7, characterized in that, The molar concentration of zinc salt in the aqueous electrolyte is 0.3 mol / L to 1.0 mol / L; And / or, the molar concentration of lithium salt in the aqueous electrolyte is 1.0 mol / L to 2.5 mol / L.
9. The aqueous electrolyte according to any one of claims 1 to 8, characterized in that, The aqueous electrolyte also includes an organic solvent; With the total volume of the aqueous electrolyte being 100%, the volume percentage of the organic solvent is less than 10%.
10. An aqueous battery, characterized in that, The aqueous battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. The electrolyte includes an aqueous electrolyte according to any one of claims 1 to 9. The positive electrode active material includes at least one of carbon-coated lithium iron phosphate, lithium iron phosphate, lithium manganese iron phosphate, or doped lithium iron phosphate. The negative electrode active material includes at least one of zinc foil, zinc sheet, zinc powder composite electrode, porous zinc electrode, zinc alloy electrode, or zinc-based material supported on a conductive substrate.